2023
DOI: 10.1177/14791641231169246
|View full text |Cite
|
Sign up to set email alerts
|

High serum Bhlhe40 levels are associated with subclinical atherosclerosis in patients with type 2 diabetes mellitus: A cross-sectional study

Abstract: Background Our previous studies have shown that the basic helix-loop-helix family member e40 (Bhlhe40) plays a critical role in regulating calcification and senescence of vascular smooth muscle cells induced by high glucose. In this study, we determined the association between serum Bhlhe40 levels and subclinical atherosclerosis in patients with type 2 diabetes mellitus (T2DM). Methods 247 patients with T2DM were included in this cross-sectional study between June 2021 and July 2022. The presence of subclinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
(21 reference statements)
0
1
0
1
Order By: Relevance
“…DDX3X [366], MAPK6 [403], ZFP36 [273], BHLHE40 [1451], TP63 [313], KRT17 [1452], CDC25B [556], SHMT2 [459], TRIB3 [444], PHGDH (phosphoglycerate dehydrogenase) [560], S100A8 [58], hsa-mir-410-3p [1453], hsa-mir-186-5p [1454], hsa-mir-432-5p [1455], BRCA1 [1456], FOXA1 [1457], CREB1 [1458], MAX (MYC associated factor X) [1459], ESR1 [1460], NFIC (nuclear factor I C) [1461] and STAT3 [1462] expression might be regarded as an indicator of susceptibility to lung cancer. DDX3X [708], BHLHE40 [1463], FKBP5 [747], TRIB3 [753], S100A8 [67], FOXA1 [1464], CREB1 [1465], SREBF2 [1466], ESR1 [1467] and STAT3 [1468] are a potential markers for the detection and prognosis of diabetes mellitus. A previous study reported that DDX3X [923], ZFP36 [882], FKBP5 [944], CDC25B [976], TRIB3 [948], hsa-mir-1277-5p [1469], MAX (MYC associated factor X) [1470] and STAT3 [1471] are altered expressed in respiratory viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…DDX3X [366], MAPK6 [403], ZFP36 [273], BHLHE40 [1451], TP63 [313], KRT17 [1452], CDC25B [556], SHMT2 [459], TRIB3 [444], PHGDH (phosphoglycerate dehydrogenase) [560], S100A8 [58], hsa-mir-410-3p [1453], hsa-mir-186-5p [1454], hsa-mir-432-5p [1455], BRCA1 [1456], FOXA1 [1457], CREB1 [1458], MAX (MYC associated factor X) [1459], ESR1 [1460], NFIC (nuclear factor I C) [1461] and STAT3 [1462] expression might be regarded as an indicator of susceptibility to lung cancer. DDX3X [708], BHLHE40 [1463], FKBP5 [747], TRIB3 [753], S100A8 [67], FOXA1 [1464], CREB1 [1465], SREBF2 [1466], ESR1 [1467] and STAT3 [1468] are a potential markers for the detection and prognosis of diabetes mellitus. A previous study reported that DDX3X [923], ZFP36 [882], FKBP5 [944], CDC25B [976], TRIB3 [948], hsa-mir-1277-5p [1469], MAX (MYC associated factor X) [1470] and STAT3 [1471] are altered expressed in respiratory viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…В окремих дослідженнях встановлено, що експресія гена Bhlhe40 може змінюватися при цукровому діабеті. Так, виявлено підвищення рівня експресії цього гена у хворих на цукровий діабет [8].…”
Section: обговоренняunclassified